Kajian Sejarah Kelembagaan Madrasah Diniyah - Sri Mundariyah (-, 2021)
Madrasah Diniyah is an Islamic Education Institution that has existed at the same time as the spread of Islam in Indonesia. The purpose of writing this article is to examine the history of madrasah diniyah institutions in Indonesia. This study uses a qualitative method with a descriptive approach. Data collection using library research method. The data analysis technique used a descriptive approach. The results of the discussion in this article regarding the history of Madrasah development in Indonesia are divided into four periods, namely 1) the colonial period, namely the Dutch colonial period and the emergence of Islamic organizations that care about Islamic education, 2) the old order period, namely at the beginning of the independence period. , madrasas are still alive, but do not get full assistance from the government, 3) the new order era, the start of government guidance on madrasas, and 4) nowadays, madrasas must immediately improve themselves and concentrate on the transformation of Islamic values.